PENGARUH PEMASARAN INTERAKTIF PRODUK SKINTIFIC MELALUI FITUR TIKTOK SHOP TERHADAP KEDARAN MEREK DAN KEPUTUSAN PEMBELIAN PADA KONSUMEN DI KOTA SEMARANG - Siti Zulfah; Trimanah .; Urip Mulyadi (Jurnal Ilmiah Penelitian Mahasiswa, 2023)
Online activities and programs that are created with the involvement of customers abd prospects sither directly or indirectly with the aim of creating sales of either produkcts or services, this is called interactice marketing. Social media is a means for consumers to obtain and share various information such as text, images, video and audio both from consumers themselves. Researchers see that there is big influence with interactive marketing carried out by Skintific products thriught the TikTok Shop feature on brand and consumer awareness in making purchasing decision in the city of Semarang. Therefore, this research aims to determine: 1) the effect in interactive marketing of Skintific product trough the TikTok sho feature on brand awareness, 2) the effect of interactive marketing of Skintific produkcts on the TikTok shop feature on purchasing decisions. This research is a quantitative research and uses positivism paradigm. The theory that will be used to analyze the problem in this sstudy is media ecology. The population used is the people of Semarang City with a sample of 100 people. The sampling technique used was purposive sampling. In the process off managing and also analyzing data, this study uses assistance from the IBM SPPS application program and uses simple linear regression anlysis. The result of this study indicate that all questionnaire items that have been tested are declared valid because r count > table (0,195), and also said to be reliable with avalue above 0.60. somple linear regression analysis ahows that there ia a significant relationship between onteractive marketing (X) on brand awareness (Y1) of 0.177 and there is a significant relationship between interactive marketing (X) on purchasing decisions (Y2) of 0.308. Keywords: Interactive Marketing, Brand awareness, Purchase Decision